The effect of preventive exercises using high-intensity interval training on the knee joint to develop some physical abilities in basketball players. (Journal of the College of Basic Education, 2025)
This study examined the effect of preventive high-intensity interval training (HIIT) exercises on some physical abilities in basketball players suffering from chronic knee pain. This problem is considered one of the major challenges affecting athletic performance, as it limits players' endurance, muscle strength, and speed, thus reducing their efficiency during matches and training. The study was conducted on a purposive sample of nine elite Iraqi basketball players suffering from chronic knee pain. An experimental approach was adopted, where the players underwent a training program based on HIIT exercises for a specified period of time, before and after the program. In addition, some physical abilities such as explosive strength, speed, and agility were measured. The study showed that high-intensity interval training (HIIT) has a positive effect in improving some physical abilities in basketball players suffering from chronic knee pain. However, the success of this type of training depends on gradual intensity, monitoring the players' responses, and its integration with rehabilitation strategies. Based on these findings, HIIT could be an effective approach to enhancing athletic performance and improving the quality of life of injured players.